Presence of microcystins in the domestic water network of Bahía Blanca city: a preliminary study (Semiárida, 2025)
In light of the difficulty in securing safe drinking water for approximately 400.000 residents in Bahía Blanca and surrounding areas (Buenos Aires, Argentina), this study aimed to evaluate whether the presence of microcystins (MCs) in the reservoir toxicologically affects the sanitary quality of the water in the domestic distribution network. In this study, the concentration of Microcystis aeruginosa cells was determined (using optical microscopy) and chlorophyll-a concentration (using spectroscopy), and quantified MC-RR, MC-YR, and MC-LR variants (using HPLC-UV). At the reservoir sampling sites, during a massive cyanobacterial bloom in March 2024, M. aeruginosa cell counts and MC-YR and MC-LR concentrations exceeded the safety limits recommended by the WHO. In April of the same year, the levels of these parameters decreased, the changes in climatic factors could have been key to the dispersal of the colonies and the variation of the toxins. The detection of MCs in the domestic network water during the massive bloom reached MC-YR values between 0,06 and 2,46 mg L-1 and MC-LR values between 0,24 and 3,25 mg L-1 at several points in the distribution network. Even after the bloom disappeared, a value of 4,16 mg L-1 of MC-YR was detected at one of the domestic network sampling sites. The presence of MCs in the network water, above the WHO's recommended maximum limit of 1 mg L-1, could be a consequence of the stability of these toxins during commonly used water purification processes and/or the potential accumulation of MCs in domestic water storage tanks. These findings highlight the need to initiate a programmed systematic study to diagnose the origin, concentration, and identity of MCs in the distribution network and domestic storage tanks.
Keywords: cyanobacteria; cyanotoxins; chlorophyll-a; HPLC